2016
DOI: 10.1186/s12864-016-2948-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study to identify potential genetic modifiers in a canine model for Duchenne muscular dystrophy

Abstract: BackgroundDuchenne muscular dystrophy (DMD) causes progressive muscle degeneration, cardiomyopathy and respiratory failure in approximately 1/5,000 boys. Golden Retriever muscular dystrophy (GRMD) resembles DMD both clinically and pathologically. Like DMD, GRMD exhibits remarkable phenotypic variation among affected dogs, suggesting the influence of modifiers. Understanding the role(s) of genetic modifiers of GRMD may identify genes and pathways that also modify phenotypes in DMD and reveal novel therapies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…mRNA is typically subject to a higher rate of turnover than many proteins, and as a consequence even genes regarded as canonically 'stable' at the protein level (such as GAPDH or beta-actin) can vary significantly between samples, and indeed alter in expression over even relatively short timeframes [24,43,44]. This inherently dynamic behaviour of mRNA, combined with the progressive pathological changes associated with DMD, the differing severity dependent on muscle type and use, and the presence of modifier genes that worsen or ameliorate disease progression all potentially place severe restrictions on the studies that may be performed; such limitations make accurate comparisons of gene expression between individuals, between muscles, or over extended time periods, particularly difficult [45].…”
Section: Introductionmentioning
confidence: 99%
“…mRNA is typically subject to a higher rate of turnover than many proteins, and as a consequence even genes regarded as canonically 'stable' at the protein level (such as GAPDH or beta-actin) can vary significantly between samples, and indeed alter in expression over even relatively short timeframes [24,43,44]. This inherently dynamic behaviour of mRNA, combined with the progressive pathological changes associated with DMD, the differing severity dependent on muscle type and use, and the presence of modifier genes that worsen or ameliorate disease progression all potentially place severe restrictions on the studies that may be performed; such limitations make accurate comparisons of gene expression between individuals, between muscles, or over extended time periods, particularly difficult [45].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant polymorphism data have been generated , while GWAS studies on this organism have successfully identified the genetic base of heritable diseases (Awano et al 2009;Bartolome et al 2015;Brinkmeyer-Langford et al 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…Only one gene was found to be among the top 10 DEGs at both time points when comparing expression levels between fast- and slow-progressing dogs. This gene, ENSCAFG00000014968, is an ortholog of peptidylprolyl isomerase a (PPIA) and was previously identified as a gene of interest in our genome-wide association study [ 19 ]. We had originally considered PPIA as a potential housekeeping gene for normalization in that previous study, but instead in that study we observed PPIA expression to be significantly different in 6- and 12-month-old GRMD compared to normal dogs in the cranial tibialis muscle.…”
Section: Resultsmentioning
confidence: 99%
“…Of the affected dogs, 3 were classified as have slow-progressing disease and 3 were classified as fast-progressing, based on measurement values for objective GRMD biomarkers [ 4 ] found to be reliable indicators of GRMD disease severity. These biomarkers included tibiotarsal joint tetanic extension (N/kg), percent eccentric contraction decrement, maximum hip flexion angle, and pelvic angle [ 19 ]. We previously identified these particular biomarkers as having genomic inflation factors (λ) of 1, meaning that measurements for these biomarkers are useful for genetic association studies because their values are independent and not biased by pedigree relationships [ 20 ].…”
Section: Methodsmentioning
confidence: 99%